Parsimonious sediment transport equations based on Bagnold's stream power approach. Issue 1 (26th September 2017) - Lammers, Roderick W.; Bledsoe, Brian P.
Abstract: It is increasingly recognized that effective river management requires a catchment scale approach. Sediment transport processes are relevant to a number of river functions but quantifying sediment fluxes at network scales is hampered by the difficulty of measuring the variables required for most sediment transport equations (e.g. shear stress, velocity, and flow depth). We develop new bedload and total load sediment transport equations based on specific stream power. These equations use data that are relatively easy to collect or estimate throughout stream networks using remote sensing and other available data: slope, discharge, channel width, and grain size. The new equations are parsimonious yet have similar accuracy to other, more established, alternatives. We further confirm previous findings that the dimensionless critical specific stream power for incipient particle motion is generally consistent across datasets, and that the uncertainty in this parameter has only a minor impact on calculated sediment transport rates. Finally, we test the new bedload transport equation by applying it in a simple channel incision model. Our model results are in close agreement to flume observations and can predict incision rates more accurately than a more complicated morphodynamic model. These new sediment transport equations are well suited for use at stream network scales, allowing quantification of this important process for river management applications. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : We developed new empirical bedload and total load sediment transport equations based on specific stream power. These equations can be used to model sediment transport processes at large spatial scales (e.g. throughout a river network) using easily obtained data on channel slope, width, discharge, and grain size. These equations are simple but accurate and can be used for catchment‐scale river management.